An ESIPT fluorescent probe and a nanofiber platform for selective and sensitive detection of a nerve gas mimic. Issue 18 (13th February 2018) - Chen, Liyan; Oh, Hyerim; Wu, Di; Kim, Myung Hwa; Yoon, Juyoung
Abstract : An ESIPT based fluorescent probe, containing a hydroxyphenyl-benzothiazole fluorophore and an oxime reaction site, serves as a selective probe for a nerve gas mimic, diethyl cyanophosphonate (DECP), in solutions and the gas phase. Abstract : An ESIPT based fluorescent probe, containing a hydroxyphenyl-benzothiazole fluorophore and an oxime reaction site, serves as a selective probe for a nerve gas mimic, diethyl cyanophosphonate (DECP), in solutions and the gas phase. The probe exhibits more than a 60-fold fluorescence enhancement in the presence of the target, has a limit of detection of 1.3 nM and displays high selectivity toward DECP over closely related substances, including sulfur mustard stimulants and other nerve agent mimics. Moreover, composite nanofibers with relatively low concentrations of the probe (0.45% w/w) exhibit distinct color and fluorescence changes upon exposure to DECP vapor.